PENINGKATAN SOSIALISASI SAFETY RIDING OLEH UNIT DIKYASA POLRES KARAWANG DALAM MENCEGAH PELANGGARAN LALU LINTAS GUNA MENCIPTAKAN KAMSELTIBCARLANTAS - Syafira, Ade Afni (Advances in Police Science Research Journal, 2020)
This research is motivated by the high traffic violations that occurred in the Karawang regency. With these problems, Dikyasa Unit Members carry out Safety Riding socialization. The purpose of this study is to find out the causes of traffic violations in Karawang Regency, the implementation of the socialization of Safety Riding by the Karawang Police Precinct unit, and the factors that influence the implementation of Safety Riding socialization. The theory used is management theory, Operant Conditioning theory. While the concept used is the Dikmas Lantas concept, the concept of Safety Riding, and the concept of traffic violations. This research was conducted using a qualitative approach, using field research methods, as well as data collection techniques by interviewing, observing, and studying documents. The results of this study indicate that breaking behavior is caused by negative attitudes possessed by these drivers. Besides subjective norms or motivations to follow the behavior of others also become one of the causes of traffic violations. The implementation of the Safety Riding socialization is carried out through the steps of planning, organizing, implementing, and controlling. While the factors that influence the socialization of Safety Riding are supporting factors and inhibiting factors. Supporting factors are method, machine, and market. The inhibiting factors are man, money, materials The author suggests that increasing the intensity of Safety Riding socialization activities aimed at private employees who work in factories and companies. Apply reward and punishment system to Unit members. Maximizing social media in providing traffic information. Make an additional number of Dikyasa Unit personnel and give Dikjur, especially to policewomen.